1992
DOI: 10.1136/gut.33.9.1289
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis complicating Crohn's disease: mere coincidence or causality?

Abstract: An example of acute pancreatitis developing five weeks after initial treatment with 5-aminosalicylic acid (5-ASA) and methylprednisolone for severe Crohn's disease is reported in a 37 year old female patient. She had undergone cholecystectomy for gall stones some years earlier. There Reduced levels of albumin (3.2 g/dl) and haematocrit (35%) and raised levels of alpha-lproteinase-inhibitor (283 mg/dl) and C-reactive protein (5.7 mg/dl) indicated acute inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…If, after routine studies with history, laboratory studies, and noninvasive imaging, there is no identifiable cause of pancreatitis, cases are often termed “idiopathic.” There are several reports of patients with no established cause of acute pancreatitis other than CD itself 1,19,21–24. Roughly one fifth of the patients in our experience had “idiopathic pancreatitis.” All other possible causes of acute pancreatitis were excluded.…”
Section: Discussionmentioning
confidence: 62%
“…If, after routine studies with history, laboratory studies, and noninvasive imaging, there is no identifiable cause of pancreatitis, cases are often termed “idiopathic.” There are several reports of patients with no established cause of acute pancreatitis other than CD itself 1,19,21–24. Roughly one fifth of the patients in our experience had “idiopathic pancreatitis.” All other possible causes of acute pancreatitis were excluded.…”
Section: Discussionmentioning
confidence: 62%
“…In most instances of canine pancreatitis, the proximate cause remains unidentified. A growing body of studies of humans with various forms of inflammatory bowel disease has demonstrated an association between inflammatory bowel disease (IBD) and pancreatitis that could be more causal than associative (Seyrig et al 1985;Tromm et al 1992;Triantafillidis et al 2004;Barthet et al 2006). The intermittent and sometimes mild nature of IBD in dogs may suggest other health problems in the clinical setting and, as a consequence, definitive diagnosis remains elusive in many instances (Hall and Simpson 2000).…”
Section: Individual Traits By Organmentioning
confidence: 97%
“…Many mechanisms have been suspected: drug treatment, [5][6][7][8][9][10][11][12][13][14][15] duodenal CD, [16][17][18][19][20] gallstones, 1 sclerosing cholangitis, 1 and idiopathic/extraintestinal manifestation. [1][2][3][4]19,[21][22][23][24] Many reports in the literature implicate medical therapy for CD (usually azathioprine, 7,12-14 6-mercaptopurine, 8,14 5-aminosalicylate drugs, [5][6][9][10][11] or metronidazole 15 ) as the most likely instigating factor. We sought to identify clinical features, potential risk factors, and clinical outcomes in a consecutive series of patients with CD evaluated at our institution and to determine if any may have presented with pancreatitis as a potential extraintestinal manifestation of CD.…”
mentioning
confidence: 99%